Signals and systems with MATLAB computing and Simulink modeling [ - Karris, Steven T. (Orchard Publications, 2008)
This text contains a comprehensive discussion on continuous and discrete time signals and systems with many MATLAB® examples. Contents: Elementary Signals, Laplace transformation and its Inverse, Circuit Analysis with the Laplace transformation, State-Space, Impulse Response and Convolution, Fourier Series and Transform, Discrete-Time Signals and the Z transform, Discrete Fourier Transform and FFT, Design of Analog and Digital Filters and Window Functions